Fitzgerald's Rubáiyát of Omar Khayyám : popularity and neglect - Poole, Adrian; Ruymbeke, C. van (Christine van); Martin, W. H. (William Henry), 1927-; Mason, Sandra (Anthem nineteenth century studies., 2011)
For all its fame in the wider world, Edward FitzGerald#x92;s #x91;Rubáiyát of Omar Khayyám#x92; (1859) has been largely ignored by the academic establishment. This volume explores the reasons for both its popularity and neglect.